If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + x + 8 = -48 Reorder the terms: 4 + 8 + x = -48 Combine like terms: 4 + 8 = 12 12 + x = -48 Solving 12 + x = -48 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + x = -48 + -12 Combine like terms: 12 + -12 = 0 0 + x = -48 + -12 x = -48 + -12 Combine like terms: -48 + -12 = -60 x = -60 Simplifying x = -60
| 30+15=2x+4 | | 8n+3a=144 | | 9/3.14= | | 6x-9=4x+4 | | .432=logx^2 | | .20/50 | | 3*7/6 | | (y-5)(-3y^2+6y+3)=0 | | 2x+4+3x=2x+3 | | 40+40y-16=13y-12-3y | | 36=3.14(4)h | | 7x-2y=-26 | | 5g+4(-5+3g)=11g | | y-1+4(3y+1)=-3(y+5) | | .4(x+2.4)=2.95 | | x=2(x-1)-6 | | -36-9=x | | 6x-2=8+5x | | 2x^2-26x+7=0 | | -5x=-33 | | 2X+3-(x-1)=2x-(-2)-(-x) | | 3/10-2x=8/2x | | 8.3=(b/14) | | 1/2(20x)-18=200 | | 4(x+5)+84=8x-4(x-6) | | [(-24)+(-8)]+13= | | -2(11)-15y=-29 | | (27b^4)^(7/3)/(9b^5)^(3/2) | | 4x-1+6=180 | | 1/5n-8=95 | | 40l-2=7 | | (-2/3)/[1/2-(1/9)] |